An Examination of Whether Incarcerated Juveniles are Entitled by the Constitution to Rehabilitative Treatment - Roth, Andrew D. (1985)
This Note attempts to resolve the arguments presented in the literature and the case law and determine whether the federal Constitution mandates a right to treatment for involuntarily incarcerated juveniles. Part I examines the varied situations that have given rise to right to treatment claims. Part II elucidates the three principal theories on which right to treatment claims have been based: (1) that because the purpose of incarcerating juveniles is to promote their welfare, rehabilitation is mandated by the due process requirement that the nature of the commitment bear some reasonable relation to the purpose for which the individual is committed ; (2) that rehabilitation is required as the quid pro quo for the reduced procedural safeguards afforded in juvenile proceedings; and (3) that confinement absent rehabilitation violates evolving standards of decency in contravention of the eighth amendment. With respect to the constitutional theories outlined above, Part III concludes (1) that rehabilitation is required by the due process clause when the state must rely on a rehabilitative purpose to justify its confinement of the juvenile, but not when the state may incarcerate the juvenile through an exercise of its police power; (2) that the reduction of procedural safeguards in juvenile proceedings should not give rise to a substantive constitutional right to rehabilitation; and (3) that rehabilitation is required by the eighth amendment where, as in (1), the state must rely on a rehabilitative purpose to justify the juvenile's confinement. The protections offered by the eighth amendment are therefore found to be coextensive with those provided by the due process clause. The Note infers from these separate conclusions that there is no single answer to the question of whether involuntarily incarcerated juveniles possess a constitutional right to rehabilitative treatment. The Note concludes that the existence of such a right depends ultimately on an evaluation of the delinquent act that led to the juvenile's incarceration